Human Resource Development Strategy in an Effort to Increase Employee Performance at PT. Pas Global Teknologi - Nur, Fauziah; Sutarto, Bambang (Kompartemen: Kumpulan Orientasi Pasar Konsumen, 2024)
This research aims to determine Human Resource Development in improving employee performance at PT Pas Global Teknologi. This type of qualitative research is used as a method in this research. The resource persons in this research were 5 employees. The data was collected through interview techniques, observation and preparation of documentation. Or it can be done using triangulation techniques, namely combining various techniques and all existing data sources. The research concluded with the result that training and human resource development activities at PT Pas Global Teknologi were carried out according to the work needs of each individual. The results of the research are (1) PT Pas Global Teknologi has made efforts to develop Human Resources to improve employee performance. The human resource development carried out by PT Pas Global Teknologi includes training, guidance and socialization between employees which is carried out for informal evaluation, namely by sharing sessions regarding employees and company team heads. (2) The performance of PT Pas Global Teknologi employees is good, this can be seen from employees who understand and carry out their duties and responsibilities at work. There are several factors to improve employee performance, namely appropriate salary or incentives, providing motivation from leaders, physical and spiritual health of employees, and good relationships between employees